Rapid and Effective Batch Adsorptive Removal of Cadmium from Domestic Wastewater Using Barium Oxide Nanorods - Tezgin, Emine; Zaman, Buse Tugba; Ozturk Er, Elif; Dalgic Bozyigit, Gamze; Turak, Fatma; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2025)
The ease of synthesis, abundant surface-active sites and cost-effectiveness make metal oxide-based nanomaterials promising adsorbents for fast and efficient removal of heavy metals. This study introduces a new metal oxide adsorbent for the removal of Cd(II) ions from domestic wastewater. Barium oxide nanorods were successfully synthesized via a simple precipitation route and characterized using X-ray diffraction (XRD), Fourier transform-infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). The batch adsorption process demonstrated high efficiency with the key parameters including solution pH (9.0), adsorbent amount (50 mg), and contact period (10 min). It was found that increasing the adsorbent amount up to the surface saturation level and adjusting the solution pH favor the removal of Cd(II) ions. The adsorption isotherm data well suited to the Langmuir model, with a determination coefficient above 0.95, suggesting a monolayer adsorption mechanism. The maximum adsorption capacity was found to be 67.54 mg/g. These findings show that barium oxide nanorods are promising adsorbents for the rapid and efficient removal of Cd(II) ions from domestic wastewater.
Keywords: Adsorption isotherm; barium oxide nanorods; cadmium; heavy metals; wastewater treatment; HEAVY-METALS REMOVAL; SELECTIVE REMOVAL; ION; NANOPARTICLES; REMEDIATION; Chemistry